2017
DOI: 10.1016/j.jcot.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Inserting pedicle screws in lumbar spondylolisthesis – The easy bone conserving way

Abstract: Our surgical technique used for high grade spondylolisthesis is safe, cost-effective, bone-preserving, reliable, and reproducible for high grade Lumber spondylolisthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is difficult for osteoporotic vertebrae to provide good pullout strength for pedicle screws due to the loss of bone mass and sparse bone trabeculae. Due to vertebral body forwards sliding and rotation, lumbar-pelvic sagittal imbalance and intervertebral instability 16 , 17 , the pullout strength of pedicle screws must be higher than that of pedicle screws during surgery, especially in isthmic spondylolisthesis. Biomechanical studies confirmed that the pullout strength of the pedicle screw was significantly reduced when the bone density was less than 0.777 ± 0.330 g/cm 2 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult for osteoporotic vertebrae to provide good pullout strength for pedicle screws due to the loss of bone mass and sparse bone trabeculae. Due to vertebral body forwards sliding and rotation, lumbar-pelvic sagittal imbalance and intervertebral instability 16 , 17 , the pullout strength of pedicle screws must be higher than that of pedicle screws during surgery, especially in isthmic spondylolisthesis. Biomechanical studies confirmed that the pullout strength of the pedicle screw was significantly reduced when the bone density was less than 0.777 ± 0.330 g/cm 2 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Isthmic spondylolisthesis is a common spinal disease that requires a higher holding power of screws due to poor spinal stability and the need for pull-up and reduction during surgery 16 , 17 . Previous studies have reported that PMMA-PSs enhance the holding power of the screws 14 , but few cases have reported their use in single-segment isthmic spondylolisthesis in osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Spondylolisthesis, a complex and challenging multifactorial condition, shows forwards slippage of one vertebra over another. It can occur at any age and one study shows the average age of 42 years [6]. It may occur both in male and female and one study shows a male to female ratio of 1.1:1 [7].…”
Section: Discussionmentioning
confidence: 99%
“…According to the pre-operative ODI score was 53.7 (±13.1) which improved to 22.5 SD 15.5 at two years follow-up [12]. The average pre-operative ODI score was 51.4, which improved to 18.6 postoperatively [6], but we have divided our patients into three groups with ODI score of 32.63 in moderate disability group while 67 in the group with crippling pain.…”
Section: Discussionmentioning
confidence: 99%